2022
DOI: 10.3389/fpsyt.2022.850794
|View full text |Cite
|
Sign up to set email alerts
|

Neural correlates of affective theory of mind in medication-free nonsuicidal self-injury: An fMRI study

Abstract: Emerging evidence indicates that emotion processing deficits are associated with nonsuicidal self-injury (NSSI). However, limited attention has been paid to the socio-affective functions of NSSI. In this study, we aimed to investigate the affective theory of mind (ToM) in medication-free individuals engaging in NSSI at both behavioral and neural levels. Twenty-eight individuals (mean age = 22.96 years) who engaged in NSSI and 38 age-, sex-, and IQ-matched controls (mean age = 22.79 years) underwent functional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 82 publications
(44 reference statements)
0
3
0
Order By: Relevance
“…The middle frontal gyrus overlaps with both the dorsal and ventral attention regions (Fox et al, 2006), suggesting that with higher lifetime NSSI episodes, individuals tend to have more attentional engagement in the context of repetitive negative thinking. Previous work has also demonstrated greater middle frontal gyrus activation in response to NSSI photographs among adolescent females with NSSI and increased superior frontal gyrus activity during an affective theory of mind task in adults with NSSI (Moon et al, 2022; Plener et al, 2012).…”
Section: Discussionmentioning
confidence: 87%
“…The middle frontal gyrus overlaps with both the dorsal and ventral attention regions (Fox et al, 2006), suggesting that with higher lifetime NSSI episodes, individuals tend to have more attentional engagement in the context of repetitive negative thinking. Previous work has also demonstrated greater middle frontal gyrus activation in response to NSSI photographs among adolescent females with NSSI and increased superior frontal gyrus activity during an affective theory of mind task in adults with NSSI (Moon et al, 2022; Plener et al, 2012).…”
Section: Discussionmentioning
confidence: 87%
“…In addition, recent studies have found that NSSI behavior is on the rise [7,8]. Neuropsychological alterations in adolescents with NSSI involve emotion dysregulation, reduced impulse control, and impaired problem solving [9][10][11][12][13]. D'Zurilla and Goldfried [14] de ned decision making (DM) as a component of problem-solving skills, which are advanced cognitive processes.…”
Section: Introductionmentioning
confidence: 99%
“…A great deal of empirical evidence has shown that individuals with NSSI, relative to controls, exhibit higher emotion dysregulation, such as limited access to regulation strategies, nonacceptance of emotional responses, and difficulties in impulse control [2,34]. More recently, along with emotion regulation problems, dysfunctions in socio-affective processing, such as emotional contagion, emotional mimicry, and affective theory of mind, have also been highlighted in those engaging in NSSI [35][36][37][38][39]. In particular, emotional contagion is closely tied to an individual's well-being and mental health [40], as the successful contagion of emotions has adaptive advantages in social species, such as humans, in allowing individuals to bond and communicate among close relationships [41][42][43].…”
Section: Introductionmentioning
confidence: 99%